Applying Cognitive Semantics to Infer Psychological Teachings From The Quran/ توظيف علم الدلالة المعرفية لاستنباط التعاليم النفسية من القرآن - Esfahani, Ali Banaeian; Rizi, Elahe Sadat Mirsafaei (Ijaz Arabi Journal of Arabic Learning, 2025)
This study applies theories of cognitive semantics to uncover psychological insights from the Quran. It focuses on conceptual metaphor theory, mental schemas, mental spaces, and embodied cognition. The research aims to understand the relationship between language and cognition in religious texts, emphasizing psychological aspects related to emotional regulation, achieving spiritual balance, and enhancing psychological resilience. A descriptive analytical approach is employed to apply these theories to Quranic texts. For example, metaphors such as "light and darkness" are analyzed as symbols of guidance and misguidance, while the "straight path" schema reflects a comprehensive spiritual journey toward ethical goals. The study also examines how conceptual blending connects abstract meanings with sensory experiences and explores the role of embodied cognition in understanding the Quran as a profound linguistic and cognitive experience. The findings highlight that applying cognitive semantic theories offers innovative tools for interpreting the Quran from a modern cognitive perspective, fostering stronger integration between Islamic studies and cognitive sciences. The study underscores the need for developing interdisciplinary frameworks to analyze religious texts and interpret their psychological and spiritual teachings within their linguistic and cultural contexts.